Fillers preparation for polymer composite and its properties â€“ a review - Vinod Kumar, T; Chandrasekaran, M; Mohanraj, P; Balasubramanian, Ravishankar; Muraliraja, R; S. Shaisundaram, V (International Journal of Engineering and Technology, 2018)
This paper is a review about the manufacture of polymer matrix composite by the filler materials, property and its preparation. Day by day the role of composite materials in industrial and household applications is increased. By using the variety of matrix, reinforcement and filler materials the polymer composite obtains from it. To improve the mechanical properties of the polymer composite, important role is played by filler materials. There is a unique property for each type of filler materials, which is altered by changing the percentage of filler materials. Filler materials important purpose is to reduce the cost of material and it increase the mechanical properties, that also use to increase surface finish and thermal property. In this paper, the elaboration of polymer materials and its uses are discussed, which held later the synthesis of polymer composite by different fillers. The filler properties, manufacture methods, polymer composite properties are discussed.Â Â